Cyclophosphazene solid electrolyte additive, modified solid electrolyte and preparation method and application thereof
By using multi-substituted cyclophosphazene compounds as additives in all-solid-state lithium batteries, combining lithium salts and polymer matrix to prepare modified solid electrolytes, the problems of deterioration of electrochemical performance and insufficient flame retardant performance of lithium batteries are solved, and excellent flame retardant performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202411499101.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The parasitic reaction of existing all-solid lithium batteries on the surface of lithium metal leads to deterioration of electrochemical properties, and the additive process of flame-retardant polymer electrolytes is cumbersome, making it difficult to meet the needs of room temperature cycle life and practical applications of solid electrolytes.
Multi-substituted cyclophosphazene compounds are used as solid electrolyte additives to prepare modified solid electrolytes by combining with lithium salts and polymer matrix, and a dense solid electrolyte membrane is formed through casting and hot pressing technology.
Excellent flame retardant performance at low additive content (5-25 wt%) is achieved, the lithium+transmission kinetics and electrochemical windows are improved, and the cycle stability and room temperature performance of all solid lithium batteries are extended.
Smart Images

Figure CN119591643A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a cyclophosphazene solid electrolyte additive, a modified solid electrolyte, and a preparation method and application thereof. More specifically, the present invention discloses a multi-substituted cyclophosphazene compound and an application thereof as a solid electrolyte additive in an all-solid-state lithium battery, a modified solid electrolyte containing the cyclophosphazene compound and a preparation method thereof, and an all-solid-state lithium battery containing the modified solid electrolyte. Background Art
[0002] All-solid-state lithium metal batteries are an important development direction for high-energy-density, long-lasting energy storage systems. Lightweight, flexible, and flame-retardant polymer electrolytes with good solid-solid interface compatibility can inhibit battery thermal runaway and significantly improve battery safety, and have become an important research direction; however, the parasitic reaction of flame-retardant polymer electrolytes on the lithium metal surface leads to the deterioration of the electrochemical performance of all-solid-state lithium metal batteries, which seriously limits the practical application of all-solid-state lithium metal batteries.
[0003] The current key research direction is to optimize the chemical composition and microstructure of the decomposition products on the surface of the lithium negative electrode by regulating the interfacial electrochemical process to form a continuous and stable solid electrolyte interface.
[0004] Studies have shown that the introduction of fluorinated film-forming additives can promote the formation of a continuous and stable fluorinated solid electrolyte interface (SEI) rich in lithium fluoride (LiF) on the surface of lithium metal by polymer electrolytes. In the prior art, by constructing a flame-retardant electrolyte copolymerized with a fluorinated flame retardant monomer, the electrolyte can form a highly stable fluorinated SEI on the surface of lithium metal, thereby improving the lithium deposition kinetics and improving the safety and electrochemical life of all-solid-state lithium batteries.
[0005] CN 108341932A discloses a flame retardant electrolyte composed of a polymer chain, a flame retardant group, a lithium ion conductive group, and a capping group; the phosphate group introduced into the electrolyte has good flame retardant properties, and the introduced ethylene oxide (EO) lithium ion conductive group is connected to Li + The continuous process of "complexation-decomplexation-recomplexation" realizes Li + Quick migration.
[0006] CN 114551996A discloses a flame retardant polymer electrolyte composed of a cyclophosphazene flame retardant, a plasticizer, a polymer substrate, a glass fiber membrane skeleton and a lithium salt; the electrolyte is prepared by ultraviolet polymerization, and while almost not affecting the ion transmission performance, the electrochemical performance is ensured while the flame retardant effect is increased, providing a guarantee for the preparation of a highly safe lithium ion battery.
[0007] CN 115084646A discloses a cyclotriphosphazene-based flame-retardant polymer electrolyte. The polymer electrolyte is composed of a cyclotriphosphazene-based cross-linked structure with flame-retardant properties as a main body and PEG-functionalized cyclotriphosphazene PEG-HCCP as an additive. The PEG-functionalized cyclotriphosphazene PEG-HCCP is used as an ion conductor and flame-retardant enhancer to simultaneously improve the flame-retardant properties and ionic conductivity of the polymer electrolyte, thereby improving the safety and electrochemical performance of the battery.
[0008] Although the above studies have attempted to improve the safety and electrochemical performance of all-solid-state lithium batteries from the perspectives of flame retardant molecular design, interface component optimization, and polymer skeleton structure regulation, the continuous parasitic reaction between the electrode and the electrolyte causes the battery performance to deteriorate rapidly. The cumbersome additive process and the current progress still cannot meet people's needs for room temperature cycle life and practical applications of solid electrolytes.
[0009] In view of this, the present invention is proposed. Summary of the invention
[0010] The object of the present invention is to provide a cyclophosphazene solid electrolyte additive, a modified solid electrolyte and a preparation method and application thereof, and more specifically, to provide a multi-substituted cyclophosphazene compound and an application thereof as a solid electrolyte additive in an all-solid-state lithium battery, a modified solid electrolyte containing the cyclophosphazene compound and a preparation method thereof, and an all-solid-state lithium battery containing the modified solid electrolyte.
[0011] Based on the above findings, the present invention provides the following technical solutions:
[0012] In one aspect, the present invention provides a polysubstituted cyclophosphazene compound, the structural formula of which is shown in (1):
[0013]
[0014] in:
[0015] R1, R2, R3, R4, R5 and R6 are each independently selected from a substituent group containing an oxygen atom and / or a halogen atom.
[0016] In the above technical solution, the substituent group containing oxygen atoms is a substituent group containing at least one of COC, Si-O-Si and CO-Ph.
[0017] In the above technical solution, the substituent group containing a halogen atom is a substituent group containing at least one of F, Cl, Br and I.
[0018] In a specific embodiment of the present invention, the polysubstituted cyclophosphazene compound has a structure as shown in the following formula (2), (3) or (4):
[0019]
[0020]
[0021] On the other hand, the present invention also provides the use of the above-mentioned multi-substituted cyclophosphazene compounds as solid electrolyte additives.
[0022] On the other hand, the present invention also provides the use of the above-mentioned multi-substituted cyclophosphazene compounds as solid electrolyte additives for preparing all-solid-state lithium batteries.
[0023] In another aspect, the present invention further provides a modified solid electrolyte, comprising:
[0024] The above-mentioned multi-substituted cyclophosphazene compound, lithium salt and polymer matrix;
[0025] Specifically, the added amount of the multi-substituted cyclophosphazene compound is 5-25 wt %.
[0026] In the above technical solution, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate and lithium tetrafluoroborate.
[0027] In the above technical solution, the polymer matrix is one or more of polyethylene oxide, polyethylene glycol and polyethylene glycol dimethyl ether.
[0028] Preferably, in the above technical solution, the average molecular weight of the polymer matrix is 400-1,000,000, preferably 100,000-600,000.
[0029] In another aspect, the present invention also provides a method for preparing the above-mentioned modified solid electrolyte, comprising:
[0030] The polymer matrix, lithium salt and multi-substituted cyclophosphazene compounds as additives are uniformly dispersed in a polar solvent, coated into a film by a cast-on method, vacuum dried to remove the solvent, and then hot pressed to form a film.
[0031] Preferably, in the above technical solution, the polar solvent is at least one of anhydrous acetonitrile, tetrahydrofuran and N,N-dimethylpyrrolidone.
[0032] Preferably, in the above technical solution, the vacuum drying temperature is 60-80°C.
[0033] Preferably, in the above technical solution, the temperature of the hot pressing molding is 80-100°C
[0034] In a specific embodiment of the present invention, the method for preparing the modified solid electrolyte comprises:
[0035] In the presence of a polar solvent, a polymer matrix, a lithium salt and a multi-substituted cyclophosphazene compound as an additive are mixed evenly, a film containing a polar solvent is obtained by a casting method, and after vacuum drying to remove the polar solvent, a dense, film-like solid electrolyte is obtained by hot pressing.
[0036] In the above technical solution, the amount of the multi-substituted cyclophosphazene compound added is controlled to control its content in the modified solid electrolyte to be 5-25wt%.
[0037] In the above technical solution, the amount of lithium salt and polymer matrix added is to control the molar ratio of lithium to oxygen to be 1:5-20, preferably 1:8-12.
[0038] Preferably, in the above technical solution, the film thickness of the solid electrolyte is 5-20 μm, preferably 10-15 μm.
[0039] Another aspect of the present invention provides an all-solid-state lithium battery, comprising a positive electrode material, the above-mentioned modified solid electrolyte and a negative electrode material compounded in sequence.
[0040] In the above technical solution, the negative electrode material is lithium metal and / or graphite.
[0041] In the above technical solution, the positive electrode material is one of lithium iron phosphate (LFP), sulfur and nickel-cobalt-manganese ternary (NCM).
[0042] Compared with the prior art, the present invention has the following advantages:
[0043] (1) The polysubstituted cyclophosphazene additive provided by the present invention can absorb a large amount of reaction heat during thermal decomposition. The phosphoric acid, metaphosphoric acid and polyphosphoric acid generated by the decomposition can form a non-volatile protective film on the surface of the polymer material to isolate the air. The PO· free radicals can combine with the H· and HO· free radicals to inhibit the combustion chain reaction. At the same time, the non-combustible gases such as carbon dioxide, ammonia, nitrogen and water vapor released after heating block the oxygen supply, thereby achieving the purpose of flame retardant synergy and synergy. That is, the modified solid electrolyte provided by the present invention can achieve excellent flame retardant performance at a relatively low additive content (5-25wt%).
[0044] (2) The polysubstituted cyclophosphazene additives provided by the present invention, on the one hand, utilize the halogen bond between the polar substituents on the cyclophosphazene and the lithium salt anion to increase the dissociation degree of the lithium salt and thus increase the carrier concentration, thereby improving the Li + Transport kinetics, improving room temperature Li + On the other hand, the conductivity of Li +Coordination structure, change the decomposition sequence of lithium salt anions, optimize the electrode-electrolyte interface components, broaden the electrochemical window, and improve the cycle stability of all-solid-state lithium batteries with high-voltage positive electrodes;
[0045] (3) The electrolyte additive of the present invention is applied to all-solid-state lithium batteries, which can ensure stable cycling of the all-solid-state batteries at 20-30°C. At 30°C, the all-solid-state lithium battery can be stably cycled for 200 cycles under the conditions of 0.1C charging and 0.5C discharging with the matching NCM811 positive electrode, and the capacity retention rate is 86.1%. Even at 20°C, the all-solid-state lithium battery can be cycled for 50 cycles under the conditions of 0.1C charging and 0.2C discharging, and the capacity retention rate is 70.0%, showing excellent cycle stability.
[0046] The present invention is a new exploration of cyclophosphazene additives in all-solid-state polymer electrolytes, providing a new type of choice for practical room-temperature all-solid-state battery systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is an optical image of the solid electrolyte described in Example 2 (size 5 cm×8 cm);
[0048] Figure 2 The self-extinguishing time test results of the solid electrolytes of Example 2 and Comparative Example 1;
[0049] Figure 3 The cycle performance diagram of the Li||NCM811 all-solid-state battery corresponding to the solid electrolytes of Example 2 and Comparative Example 1 at 30°C (at a charging current of 0.1C and a discharging current of 0.5C);
[0050] Figure 4 The cycle performance diagram of the Li||NCM811 all-solid-state battery corresponding to Example 2 at 20°C (at a charging current of 0.1C and a discharging current of 0.2C);
[0051] Figure 5 The O1s high-resolution X-ray photoelectron spectroscopy (XPS) graphs of the SEI of Example 2 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments.
[0053] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0054] In the examples, unless otherwise specified, all the means used are conventional means in the art.
[0055] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions shall be followed; if no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.
[0056] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0057] The embodiments of the present invention provide a solid electrolyte cyclophosphazene additive, a modified solid electrolyte, and a preparation method and application thereof. More specifically, a multi-substituted cyclophosphazene compound and an application thereof as a solid electrolyte additive in an all-solid-state lithium battery, a modified solid electrolyte containing the cyclophosphazene compound and a preparation method thereof, and an all-solid-state lithium battery containing the modified solid electrolyte are provided.
[0058] Specifically, the structural formula of the polysubstituted cyclophosphazene compound is as follows:
[0059]
[0060] Wherein, R1, R2, R3, R4, R5 and R6 are each independently selected from a substituent group containing oxygen atoms and / or halogen atoms.
[0061] Specifically, the substituent group containing an oxygen atom is a substituent group containing at least one of COC, Si-O-Si and CO-Ph, and the substituent group containing a halogen atom is a substituent group containing at least one of F, Cl, Br and I.
[0062] The polysubstituted cyclophosphazene compounds provided in the embodiments of the present invention have a wide range of applications. An embodiment is exemplified for illustrative purposes only, but the scope of the present invention is not limited thereby. According to a preferred embodiment of the present invention, the cyclophosphazene compounds of the present invention can be used as solid electrolyte additives or liquid electrolyte additives, and can achieve high ionic conductivity and good interfacial mass transfer kinetics of all-solid-state batteries.
[0063] In an embodiment of the present invention, the modified solid electrolyte includes a multi-substituted cyclophosphazene compound, a lithium salt and a polymer matrix.
[0064] According to a preferred embodiment of the present invention, in the modified solid electrolyte, the added amount of the multi-substituted cyclophosphazene compound is 5-25 wt %.
[0065] According to a preferred embodiment of the present invention, in the modified solid electrolyte, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate and lithium tetrafluoroborate.
[0066] According to a preferred embodiment of the present invention, in the modified solid electrolyte, the amount of lithium salt added is to control the molar ratio of lithium to oxygen to be 1:5-20, preferably 1:8-12.
[0067] According to a preferred embodiment of the present invention, in the modified solid electrolyte, the polymer matrix is one or more of polyethylene oxide, polyethylene glycol and polyethylene glycol dimethyl ether.
[0068] Preferably, in the above technical solution, the average molecular weight of the polymer matrix is 400-1,000,000, preferably 100,000-600,000.
[0069] An embodiment of the present invention provides a method for preparing a modified solid electrolyte, specifically, uniformly dispersing a polymer matrix, a lithium salt and a multi-substituted cyclophosphazene additive in a polar solvent, obtaining a solvent-containing film by a casting method, and obtaining a dense, film-like solid electrolyte by hot pressing after removing the solvent by vacuum drying.
[0070] In the embodiments of the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the polar solvent. An implementation mode is exemplified, but the scope of the present invention is not limited thereby. The polar solvent is at least one of anhydrous acetonitrile, tetrahydrofuran and N,N-dimethylpyrrolidone.
[0071] In the embodiments of the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the process operation temperature. Generally, the vacuum drying temperature is 60-80°C, and the hot pressing molding temperature is 80-100°C.
[0072] In the embodiments of the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the film thickness of the solid electrolyte. Generally, the film thickness of the solid electrolyte is 5-20 μm, preferably 10-15 μm.
[0073] In the embodiment of the present invention, the type of negative electrode active material of the all-solid-state lithium battery can be selected from a wide range, and commonly used negative electrode active materials can be used in the present invention. An implementation method is exemplified, but the scope of the present invention is not limited thereby. The negative electrode active material is lithium metal and / or graphite.
[0074] In the embodiments of the present invention, commonly used positive electrodes can achieve the purpose of the present invention, and there are no special requirements for the composition of the positive electrode active material layer of the positive electrode. It is worth mentioning that an electrolyte component is generally added to the positive electrode active material layer, and the electrolyte composition described in the present invention is preferably added. There are no special requirements for the positive electrode active material, conductive agent type, binder and other materials of the positive electrode active material layer and their specific composition.
[0075] For example, the positive electrode active material is selected from one of lithium iron phosphate (LFP), sulfur and nickel cobalt manganese (NCM); the conductive agent is selected from one or more of Ketjen black, carbon nanotubes and graphene.
[0076] In addition, there are no special requirements for the specific composition formula of the positive electrode active material layer. Generally, the mass ratio of the positive electrode active material LFP, electrolyte, and conductive agent is 5-8:1-3:1-1.5.
[0077] In the embodiment of the present invention, the compaction density of the positive electrode can be selected in a wide range, which is an exemplary embodiment, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the compaction density of the positive electrode is 2.5-3.0 g / cm 3 .
[0078] In the embodiment of the present invention, the loading amount of the active material layer can be selected in a wide range based on the loading amount of the positive electrode active material, which is an exemplary embodiment, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the loading amount of the positive electrode active material layer is 2.0-6.0 mg / cm 2 The above technical solution has the advantages of high discharge specific capacity and good cycle stability.
[0079] In the present invention, there are no special requirements for the preparation methods of the positive electrode and the negative electrode, and they will not be described in detail here.
[0080] The organic solvents and lithium salt electrolytes used in the embodiments of the present invention and the comparative examples are all of battery grade; the ether-based polymer electrolyte solutions involved in the embodiments of the present invention are all prepared in a glove box in an argon atmosphere with H2O and O2 contents lower than 0.01ppm, the positive electrode, negative electrode, solid electrolyte and other battery components are strictly dried, and the solution preparation and battery assembly are carried out at room temperature.
[0081] In the following examples and comparative examples, the active material surface loading of the battery positive electrode is 3.0 mg / cm 2 ; In the following examples and comparative examples, 0.1C / 0.2C means charging at a rate of 0.1C and discharging at a rate of 0.2C; In the following examples and comparative examples, 0.1C / 0.5C means charging at a rate of 0.1C and discharging at a rate of 0.5C.
[0082] Example 1
[0083] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 600,000 were weighed in a glove box, added to 15 ml of anhydrous acetonitrile, and stirred evenly; then 0.1 g of a fluorinated siloxane-substituted cyclotriphosphazene additive shown in the following formula was added to the above solution, and mixed thoroughly;
[0084]
[0085] The film is formed by a casting method, vacuum dried at 80°C, and hot-pressed at 80°C to form a dense solid electrolyte membrane.
[0086] The preparation method of the positive electrode includes: using a general preparation method, the positive electrode active material NCM811, the electrolyte composition (the materials of bistrifluoromethanesulfonyl imide lithium, polyethylene oxide with a number average molecular weight of 600000 and cyclotriphosphazene additive substituted by fluorinated siloxane are the same as above, the ratio is 8:12:1, and the preparation process is the same as above), and the conductive agent Ketjen black are uniformly dispersed in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, a planetary mixer is used to form a uniform slurry, the slurry is applied to the surface of the current collector by a scraper, and it is pre-dried in a 70°C forced air drying oven for 4 hours, and then treated in a 70°C vacuum drying oven for 12 hours to remove the residual solvent. The obtained positive electrode sheet is controlled to have a compaction density of 2.5g / cm by a roller press. 3 .
[0087] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0088] Example 2
[0089] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 600,000 were weighed in a glove box, added to 15 ml of anhydrous acetonitrile, and stirred evenly; then 0.4 g of a fluorinated siloxane-substituted cyclotriphosphazene additive as shown in the following formula was added to the above solution, and mixed thoroughly;
[0090]
[0091] The film is formed by a casting method, vacuum dried at 80°C, and hot-pressed at 80°C to form a dense solid electrolyte membrane.
[0092] The preparation method of the positive electrode includes: using a general preparation method, the positive electrode active material NCM811, the electrolyte composition (the materials of bistrifluoromethanesulfonyl imide lithium, polyethylene oxide with a number average molecular weight of 600000 and cyclotriphosphazene additive substituted by fluorinated siloxane are the same as above, the ratio is 2:3:1, and the preparation process is the same as above), and the conductive agent Ketjen black are uniformly dispersed in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, a planetary mixer is used to form a uniform slurry, the slurry is applied to the surface of the current collector by a scraper, and it is pre-dried in a 70°C forced air drying oven for 4 hours, and then treated in a 70°C vacuum drying oven for 12 hours to remove the residual solvent. The obtained positive electrode sheet is controlled to have a compaction density of 2.5g / cm by a roller press. 3 .
[0093] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0094] Example 3
[0095] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 600,000 were weighed in a glove box, added to 15 ml of anhydrous acetonitrile, and stirred evenly; then 0.6 g of a fluorinated siloxane-substituted cyclotriphosphazene additive shown in the following formula was added to the above solution, and mixed thoroughly;
[0096]
[0097] The film is formed by a casting method, vacuum dried at 80°C, and hot-pressed at 80°C to form a dense solid electrolyte membrane.
[0098] The preparation method of the positive electrode includes: using a general preparation method, the positive electrode active material NCM811, the electrolyte composition (the materials of bistrifluoromethanesulfonyl imide lithium, polyethylene oxide with a number average molecular weight of 600000 and cyclotriphosphazene additive substituted by fluorinated siloxane are the same as above, the ratio is 4:6:3, and the preparation process is the same as above), and the conductive agent Ketjen black are uniformly dispersed in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, a planetary mixer is used to form a uniform slurry, the slurry is applied to the surface of the current collector by a scraper, and it is pre-dried in a 70°C forced air drying oven for 4 hours, and then treated in a 70°C vacuum drying oven for 12 hours to remove the residual solvent. The obtained positive electrode sheet is controlled to have a compaction density of 2.5g / cm by a roller press. 3 .
[0099] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0100] Example 4
[0101] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 100,000 were weighed and added to 15 ml of anhydrous acetonitrile in a glove box, and stirred evenly.
[0102] Then add 0.4 g of a fluorinated siloxane-substituted cyclotriphosphazene additive as shown in the following formula to the above solution and mix thoroughly;
[0103]
[0104] The film is formed by a casting method, vacuum dried at 80°C, and hot-pressed at 80°C to form a dense solid electrolyte membrane.
[0105] The preparation method of the positive electrode includes: using a general preparation method, the positive electrode active material NCM811, the electrolyte composition (the materials of bistrifluoromethanesulfonyl imide lithium, polyethylene oxide with a number average molecular weight of 100,000 and cyclotriphosphazene additive substituted by fluorinated siloxane are the same as above, the ratio is 2:3:1, and the preparation process is the same as above), and the conductive agent Ketjen black are uniformly dispersed in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, a planetary mixer is used to form a uniform slurry, the slurry is applied to the surface of the current collector by a scraper, and pre-dried in a 70°C forced air drying oven for 4 hours, and then treated in a 70°C vacuum drying oven for 12 hours to remove the residual solvent, and the obtained positive electrode sheet is controlled to have a compaction density of 2.5g / cm by a roller press. 3 .
[0106] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0107] Example 5
[0108] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.0 g of polyethylene oxide with a number average molecular weight of 600,000 were weighed in a glove box, added to 15 ml of anhydrous acetonitrile, and stirred evenly; then 0.36 g of a fluorinated siloxane-substituted cyclotriphosphazene additive shown in the following formula was added to the above solution, and mixed thoroughly;
[0109]
[0110] The film is formed by a casting method, vacuum dried at 80°C, and hot-pressed at 80°C to form a dense solid electrolyte membrane.
[0111] The preparation method of the positive electrode includes: using a general preparation method, the positive electrode active material NCM811, the electrolyte composition (the materials of bistrifluoromethanesulfonyl imide lithium, polyethylene oxide with a number average molecular weight of 600000 and cyclotriphosphazene additive substituted by fluorinated siloxane are the same as above, the ratio is 4:5:1.8, and the preparation process is the same as above), and the conductive agent Ketjen black are uniformly dispersed in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, a planetary mixer is used to form a uniform slurry, the slurry is applied to the surface of the current collector by a scraper, and pre-dried in a 70°C forced air drying oven for 4 hours, and then treated in a 70°C vacuum drying oven for 12 hours to remove the residual solvent, and the obtained positive electrode sheet is controlled to have a compaction density of 2.5g / cm by a roller press. 3 .
[0112] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0113] Example 6
[0114] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 600,000 were weighed in a glove box, added to 15 ml of anhydrous acetonitrile, and stirred evenly; then 0.4 g of a hexafluoroisopropoxycyclotriphosphazene additive shown in the following formula was added to the above solution, and mixed thoroughly;
[0115]
[0116] The film is formed by a casting method, vacuum dried at 80°C, and hot-pressed at 80°C to form a dense solid electrolyte membrane.
[0117] The preparation method of the positive electrode includes: using a general preparation method, uniformly dispersing the positive electrode active material NCM811, the electrolyte composition (lithium bistrifluoromethanesulfonyl imide, polyethylene oxide with a number average molecular weight of 600,000 and hexafluoroisopropoxy cyclotriphosphazene additive as above, the ratio is 2:3:1, the preparation process is the same as above), and the conductive agent Ketjen black in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, forming a uniform slurry by a planetary mixer, applying the slurry on the surface of the current collector by a scraper, pre-drying in a 70°C forced air drying oven for 4 hours, and then treating in a 70°C vacuum drying oven for 12 hours to remove the residual solvent, and the obtained positive electrode sheet is controlled to have a compaction density of 2.5 g / cm by a roller press. 3 .
[0118] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0119] Example 7
[0120] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 600,000 were weighed in a glove box, added to 15 ml of anhydrous acetonitrile, and stirred evenly; then 0.4 g of pentafluoro(phenoxy)cyclotriphosphazene additive shown in the following formula was added to the above solution, and mixed thoroughly;
[0121]
[0122] The film is formed by a casting method, vacuum dried at 80°C, and hot-pressed at 80°C to form a dense solid electrolyte membrane.
[0123] The preparation method of the positive electrode includes: using a general preparation method, the positive electrode active material LFP, the electrolyte composition (lithium bistrifluoromethanesulfonyl imide, polyethylene oxide with a number average molecular weight of 600000 and pentafluoro (phenoxy) cyclotriphosphazene additive are the same as above, the ratio is 2:3:1, and the preparation process is the same as above), and the conductive agent Ketjen black are uniformly dispersed in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, a planetary mixer is used to form a uniform slurry, the slurry is applied to the surface of the current collector by a scraper, and pre-dried in a 70°C forced air drying oven for 4 hours, and then treated in a 70°C vacuum drying oven for 12 hours to remove the residual solvent. The obtained positive electrode sheet is controlled to have a compaction density of 2.5g / cm by a roller press. 3 .
[0124] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0125] Example 8
[0126] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 600,000 were weighed in a glove box, added to 15 ml of anhydrous acetonitrile, and stirred evenly; then 0.4 g of a fluorinated siloxane-substituted cyclotriphosphazene additive as shown in the following formula was added to the above solution, and mixed thoroughly;
[0127]
[0128] The film is formed by a casting method, vacuum dried at 80°C, and hot-pressed at 80°C to form a dense solid electrolyte membrane.
[0129] The preparation method of the positive electrode includes: using a general preparation method, the positive electrode active material LFP, the electrolyte composition (lithium bistrifluoromethanesulfonyl imide, polyethylene oxide with a number average molecular weight of 600000 and cyclotriphosphazene additive substituted by fluorinated siloxane are the same as above, the ratio is 2:3:1, and the preparation process is the same as above), and the conductive agent Ketjen black are uniformly dispersed in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, a planetary mixer is used to form a uniform slurry, the slurry is applied to the surface of the current collector by a scraper, and pre-dried in a 70°C forced air drying oven for 4 hours, and then treated in a 70°C vacuum drying oven for 12 hours to remove the residual solvent. The obtained positive electrode sheet is controlled to have a compaction density of 2.5g / cm by a roller press. 3 .
[0130] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0131] Comparative Example 1
[0132] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 600,000 were measured in a glove box, added to 15 ml of anhydrous acetonitrile, stirred evenly, formed into a film by a casting method, vacuum dried at 80°C, and formed into a dense solid electrolyte membrane by a hot pressing method at 80°C; the difference from Example 1 is that the comparative example 1 does not add the fluorinated siloxane-substituted cyclotriphosphazene additive.
[0133] The preparation method of the positive electrode includes: using a general preparation method, uniformly dispersing the positive electrode active material NCM811, the electrolyte composition (the material of lithium bis(trifluoromethanesulfonyl imide) and polyethylene oxide with a number average molecular weight of 600,000 as above, the ratio is 1:1.5, and the preparation process is the same as above), and the conductive agent Ketjen black in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, forming a uniform slurry by a planetary mixer, applying the slurry on the surface of the current collector by a scraper, pre-drying in a 70°C forced air drying oven for 4 hours, and then treating in a 70°C vacuum drying oven for 12 hours to remove the residual solvent, and the obtained positive electrode sheet is controlled to have a compaction density of 2.5 g / cm by a roller press. 3 .
[0134] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0135] Comparative Example 2
[0136] Under argon protection, 0.8 g of lithium bis(trifluoromethanesulfonyl)imide and 1.2 g of polyethylene oxide with a number average molecular weight of 600,000 were weighed in a glove box, added to 15 ml of anhydrous acetonitrile, and stirred evenly; then 0.4 g of a hexafluorocyclotriphosphazene additive shown in the following formula was added to the above solution, and mixed thoroughly;
[0137]
[0138] The film is formed by a casting method, vacuum dried at 70°C, and hot-pressed at 70°C to form a dense solid electrolyte membrane.
[0139] The preparation method of the positive electrode includes: using a general preparation method, the positive electrode active material NCM811, the electrolyte composition (the materials of bistrifluoromethanesulfonyl imide lithium, polyethylene oxide with a number average molecular weight of 600000 and cyclotriphosphazene additive substituted by fluorinated siloxane are the same as above, the ratio is 2:3:1, and the preparation process is the same as above), and the conductive agent Ketjen black are uniformly dispersed in anhydrous acetonitrile at a mass ratio of 6:2.5:1.5, a planetary mixer is used to form a uniform slurry, the slurry is applied to the surface of the current collector by a scraper, and it is pre-dried in a 70°C forced air drying oven for 4 hours, and then treated in a 70°C vacuum drying oven for 12 hours to remove the residual solvent. The obtained positive electrode sheet is controlled to have a compaction density of 2.5g / cm by a roller press. 3 .
[0140] The positive electrode sheet, solid electrolyte membrane and lithium sheet (thickness 50μm) are assembled into an all-solid-state lithium battery; the operation process is as follows: the stamped lithium sheet (diameter 14mm) is glued to the electrolyte membrane (diameter 19mm), and then the positive electrode sheet (diameter 12mm) is glued to the other side of the electrolyte membrane, and packaged with a 2032 button battery shell, and the packaging pressure is controlled to 600kg.
[0141] Battery cycle performance test
[0142] In the embodiment of the present invention, the all-solid-state lithium battery is first placed in a 60°C oven overnight, and is charged and discharged for three cycles at 0.1C, 3.0V-4.3V (Li||NCM) / 2.8V-3.8V (Li||LFP) at 60°C, and then the electrochemical performance is tested.
[0143] The test and characterization results are shown in Table 1 and Figure 1-5 .
[0144] Table 1
[0145]
[0146] Figure 1 This is an optical image of the solid electrolyte described in Example 2 (size 5 cm×8 cm). It can be seen from the figure that the prepared solid electrolyte exhibits self-supporting properties and has uniform film formation.
[0147] Take the solid electrolyte of Example 2 and Comparative Example 1 with a size of 2 cm×5 cm, start timing after the solid electrolyte is ignited, and stop timing until it extinguishes itself, and obtain the self-extinguishing time of the solid electrolyte. The results are as follows: Figure 2 As shown in the figure, it can be seen that the solid electrolyte of Comparative Example 1 is completely burned out after ignition, while the solid electrolyte of Example 2 does not show obvious combustion loss, indicating that the solid electrolyte of Example 2 has excellent self-extinguishing performance.
[0148] Figure 3 30°C is a cycle performance diagram of the Li||NCM811 all-solid-state battery corresponding to the solid electrolytes of Example 2 and Comparative Example 1 (charge and discharge are performed at a charging current of 0.1C and a discharge current of 0.5C). It can be seen from the figure that the Li||NCM811 all-solid-state battery of Example 2 has excellent cycle stability, while the battery capacity of the Li||NCM811 all-solid-state battery of Comparative Example 1 decays rapidly, indicating that the cyclophosphazene derivative additive can significantly improve the high-voltage resistance of the electrolyte.
[0149] Figure 4 This is the cycle performance diagram of the Li||NCM811 all-solid-state battery corresponding to Example 2 at 20°C (charging and discharging at a charging current of 0.1C and a discharge current of 0.2C). It can be seen from the figure that the Li||NCM811 all-solid-state battery of Example 2 exhibits excellent cycle performance below room temperature.
[0150] Figure 5 The O1s high-resolution X-ray photoelectron spectroscopy (XPS) diagram of the SEI of Example 2 and Comparative Example 1 (the all-solid-state battery after 50 cycles was disassembled in an argon atmosphere glove box to obtain a lithium metal negative electrode). It can be seen from the figure that compared with Comparative Example 1, the LiF component in the SEI formed in Example 2 is significantly increased, and the organic component is significantly reduced. The formed customized SEI can improve the stability of the electrode interface and ensure long cycle performance.
[0151] From the above results, it can be seen that the modified solid electrolyte of the present invention can achieve excellent flame retardant performance at a lower additive content (5-25wt%), and the all-solid-state lithium battery using the modified solid electrolyte of the present invention has better high-voltage positive electrode cycle stability and room temperature performance. The solid state of the present invention can form a dense and stable LiF-rich solid electrolyte interface film on the electrode surface, significantly reducing the interface impedance and improving the room temperature performance and cycle stability.
[0152] The above-mentioned embodiments only express several implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it should not be understood as limiting the scope of the invention patent.
[0153] It should be noted that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A polysubstituted cyclophosphazene compound, characterized in that: Its structural formula is shown in (1): in: R1, R2, R3, R4, R5 and R6 are each independently selected from a substituent group containing an oxygen atom and / or a halogen atom.
2. The polysubstituted cyclophosphazene compound according to claim 1, characterized in that The substituent group containing an oxygen atom is a substituent group containing at least one of COC, Si-O-Si and CO-Ph; And / or, the halogen atom-containing substituent group is a substituent group containing at least one of F, Cl, Br and I.
3. Use of the polysubstituted cyclophosphazene compound according to claim 1 or 2 as a solid electrolyte additive.
4. Use of the multi-substituted cyclophosphazene compound according to claim 1 or 2 as a solid electrolyte additive for preparing an all-solid-state lithium battery.
5. A modified solid electrolyte, characterized in that: include: The polysubstituted cyclophosphazene compound, lithium salt and polymer matrix according to claim 1 or 2; Wherein, the added amount of the multi-substituted cyclophosphazene compound is 5-25wt%.
6. The modified solid electrolyte according to claim 5, characterized in that The lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate and lithium tetrafluoroborate; and / or, the polymer matrix is one or more of polyethylene oxide, polyethylene glycol and polyethylene glycol dimethyl ether; Preferably, the average molecular weight of the polymer matrix is 400-1,000,000, preferably 100,000-600,000.
7. The method for preparing the modified solid electrolyte according to claim 5 or 6, characterized in that: include: The polymer matrix, lithium salt and multi-substituted cyclophosphazene compound as an additive are uniformly dispersed in a polar solvent, coated into a film by a cast-film method, vacuum dried to remove the solvent, and then hot pressed to form; Preferably, the polar solvent is at least one of anhydrous acetonitrile, tetrahydrofuran and N,N-dimethylpyrrolidone. Preferably, the temperature of the vacuum drying is 60-80°C, and the temperature of the hot pressing molding is 80-100°C.
8. The method for preparing the modified solid electrolyte according to claim 7, characterized in that: The amount of the multi-substituted cyclophosphazene compound added is to control its content in the modified solid electrolyte to be 5-25wt%; The lithium salt and the polymer matrix are added in such an amount that the molar ratio of lithium to oxygen is controlled to be 1:5-20, preferably 1:8-12.
9. An all-solid-state lithium battery, characterized in that: It comprises a positive electrode material, a modified solid electrolyte as claimed in claim 5 or 6 and a negative electrode material which are compounded in sequence.
10. The all-solid-state lithium battery according to claim 9, characterized in that: The negative electrode material is lithium metal and / or graphite; The positive electrode material is one of lithium iron phosphate, sulfur and nickel-cobalt-manganese ternary.
Citation Information
Patent Citations
Functional polymer, polymer electrolyte membrane, flame-retardant polymer electrolyte composite membrane and preparation method thereof, and lithium ion battery
CN108341932A
Cyclotriphosphazene-based flame-retardant polymer electrolyte as well as preparation method and application thereof
CN115084646A
Nonaqueous electrolyte and nonaqueous electrolyte battery
CN106025306A
Cyclophosphazene flame retardant and preparation method thereof
CN106496274A
Silanol containing phosphazene compound, flame retardant, epoxy resin composition and composite metallic substrate
CN107337694A